2015
DOI: 10.15537/smj.2015.7.11453
|View full text |Cite
|
Sign up to set email alerts
|

Hyperhomocysteinemia as a metabolic disorder parameter is independently associated with the severity of coronary heart disease

Abstract: Objectives:To study the associations between hyperhomocysteinemia (HHcy) and the severity of coronary heart disease (CHD).Methods:We retrospectively analyzed metabolic parameters, anthropometric variables, and life style habits in 292 CHD patients of different categories, and 100 controlled non-CHD patients with chest pain symptoms who were hospitalized in the Department of Cardiovascular Medicine, Sichuan Academy of Medical Sciences and Sichuan Provincial People’s Hospital, Chengdu, China between October 2013… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…[ 20 , 21 ] A recently published study from China that included 292 CAD patients of different categories, and 100 non-CAD controls concluded that HHcy is independently associated with the severity of CHD, and significantly correlated with low folic acid levels in CAD patients. [ 10 ] The above findings suggest a possible association between T genotype of MTHFR C677T gene, higher circulating Hcy, lower FA levels, and more severe coronary lesions. These results warrant interventions aimed at lowering of Hcy levels in high-risk patients, particularly in those with T genotype of MTHFR C677T gene.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…[ 20 , 21 ] A recently published study from China that included 292 CAD patients of different categories, and 100 non-CAD controls concluded that HHcy is independently associated with the severity of CHD, and significantly correlated with low folic acid levels in CAD patients. [ 10 ] The above findings suggest a possible association between T genotype of MTHFR C677T gene, higher circulating Hcy, lower FA levels, and more severe coronary lesions. These results warrant interventions aimed at lowering of Hcy levels in high-risk patients, particularly in those with T genotype of MTHFR C677T gene.…”
Section: Discussionmentioning
confidence: 94%
“…[ 8 ] A recent randomized controlled trial in China demonstrated that additional administration of folic acid, an intervention for lowering circulating Hcy level, to hypertensive patients on enalapril significantly reduced the risk of first stroke in patients. [ 9 ] Although pilot studies have suggested that HHcy may be a risk factor for CAD, [ 10 ] the association between homocysteine and the severity of coronary lesions, particularly in patients with ACS, has rarely been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Folate and VB12 are two vital regulators of the metabolism of Hcy [43]. A significant association is observed between maternal lower folate concentrations and higher Hcy levels as well as an increase in the risk of preeclampsia [44].…”
Section: Discussionmentioning
confidence: 99%
“…Akyurek et al disclosed a higher serum homocysteine level in a STEMI group than in a healthy control group (19.0 ± 3.6 vs. 15.8 ± 4.2 μmol/L, p = 0.008) [ 10 ]. Liu C et al found that the prevalence of hyperhomocysteinemia (> 15 μmol/L) was higher among patients with ischemic heart disease than among controls (79.1% vs. 5%) [ 29 ], and the serum homocysteine level was positively correlated with severity (acute myocardial infarction 23.44 ± 5.78 μmol/L, unstable angina 22.62 ± 6.37 μmol/L, stable angina 18.63 ± 6.73 μmol/L, and control 10.81 ± 4.62 μmol/L, p < 0.001) [ 30 ]. In contrast, our study showed that there was no difference in serum homocysteine levels between the control and STEMI groups, and our cohort had a mean level of homocysteine markedly lower than the levels reported in previous studies.…”
Section: Discussionmentioning
confidence: 99%